Removal of phosphorus from a synthetic water solution by adsorbing onto brick waste applied to fixed bed column - Nur Hazwani Anuar, 1992-; Mohamad Ali Fulazzaky, supervisor; Fakulti Kejuruteraan Awam (2015)
Project Paper (Sarjana Muda (Kejuruteraan Awam - Alam Sekitar))- Universiti Teknologi Malaysia, 2015